FILSAFAT MANUSIA DALAM MEMETIKA RICHARD BRODIE (Pengaruh Iklan Komersial terhadap Kesadaran dan Kebebasan Manusia) - Emi Atriasari Rahmadi (Jurnal Filsafat "WISDOM", 2010)
AbstractThis study is using Richard Brodie’s memetic approach to analyze commercial advertisement, start from how the mechanism of spreading ideas used in commercial advertisement, to how the products of that mechanism could penetrate human consciousness and influenced their life as a whole.From the research regard to related issues, I figured out commercial advertisement has been used memetic principles in their production, thus at the end turned commercial advertisement into a meme that’s ready to infect human mind so that more copies of that particular meme will be generated and construct a new culture. I also construed Richard Brodie’s Memetic as philosophical, as I found the values and elements of philosophy of human, those are consciousness, free will and determinism. It has been ascertained that commercial advertisement has been pervaded into human consciousness and determined their thinking process, which also means commercial advertisement could influence human free will and determination.Keywords: memetic, Richard Brodie, commercial advertisement,meme, evolution, consciousness, free will, and determinism.